An age perspective on economic well-being and social protection in nine OECD countries - Thai-Thanh Dang; Herwig Immervoll; Daniela Mantovani; Kristian Orsini; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper quantifies the economic well-being of different age groups and the extent of their reliance on incomes from public and private sources. The aim is to establish how social benefits, and the taxes needed to finance them, affect income levels and disparities across different age groups. Results are compared across nine OECD countries using household micro-data and microsimulation models to illustrate the influence of market income patterns, household structures and social protection measures on the income distribution among and between different age groups. We use information from the late 1990s to establish a “distributional baseline” that refers to an early phase of the projected increase in dependency ratios and also pre-dates some of the major reforms that are introduced to address these. Results even for this period show that social protection was already largely “old-age” protection, with those aged 65 and over typically receiving almost three times the (net) cash transfers of the average person. In most countries, the incidence of “low” incomes was nevertheless higher among old-age individuals than for the population as a whole. We argue, however, that the cross-country evidence suggests some scope for re-balancing social protection spending without necessarily compromising distributional objectives.
Keywords: C81; D31; H22; H55; 330; inequality; poverty; social protection; ageing; demographics; microsimulation